Tinjauan Yuridis Pertanggung Jawaban Jabatan Notaris terhadap Pembuatan Akta Perjanjian Pengikatan Jual Beli (PPJB) dan Kuasa Menjual (SKM) menurut Peraturan Perundang–Undangan No. 2 Tahun 2014 (Studi Kasus 54/Pdt.G/2020/Pn) - Bakhtar, Suci Sukma Paramitha; Nugroho, Meysita Arrum (Postulat, 2025)
One of the notary's authorities is in terms of making a Deed of Sale and Purchase Agreement. The Notary can be responsible for a Sale and Purchase Agreement that is not in accordance with the provisions of the Notary Office Law if: 1. The deed he made is legally defective, 2. The Notary deliberately does not read the deed made in front of the witnesses. The notary has the duty to prepare the deed and provide advice to the parties. The notary not only certifies the signature, but also has to give advice if anything deviates from what the parties want. Checking the details of the deed of agreement made and reading the deed before it is signed by the parties is a control for the parties and the notary. Thus, the deed made is the will of the parties present. The problem examined in this writing is: What is the legal position of a notary if it is associated with the notary's errors and negligence in making the deed, one of which is the deed of the Sale and Purchase Agreement. In this study, the method used is normative juridical law with an analytical approach. Based on the results of the discussion on and the results of the research, namely: The Responsibility of Notaries for the Errors and Negligence of Notaries in the Preparation of Binding Sale and Purchase Agreement deeds based on the obligations of Notaries based on Law Number 2 of 2014 concerning Notary Positions. This is to avoid losses to other parties and in accordance with Article 16 paragraph (1) letter (a) of Law of the Republic of Indonesia Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Notary Position (hereinafter referred to as UUJN), in carrying out their positions, Notaries are obliged to act trustfully, honestly, thoroughly, independently, impartially, and maintain the interests of related parties in legal act.